Pengaruh Promosi Media Sosial, Kualitas Produk dan Store Atmosphere terhadap Keputusan Pembelian Produk Fashion : (Survei pada Konsumen Abvistore di Kecamatan Tanon Sragen) - Ovitalia Afanda Riani; Retno Susanti (Pusat Riset dan Inovasi Nasional, 2024)
This research was conducted with the purpose of analyzing the significance of the influence of social media promotions, product quality and store atmosphere on purchasing decisions for Abvistore fashion products in Tanon District, Sragen. The population of this research is consumers of the Abvistore Shop in Tanon District, Sragen. The sample in this study was 137 people with the sampling technique used was accidental sampling. The data collection method in this research used a questionnaire. The data analysis techniques used are validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, t-test, F-test and R Square test. The result of the analysis stated that all questionnaire items as research instruments were valid and reliable, and the classical assumption test, both multicolinearity test, autocorrelation test, heteroscedasticity test, and normality test of variables were declared to passed the classical assumption test. Multiple linear regression showed that all regression coefficients were positive, which means that variable X1 (social media promotion), X2 (product quality) and X3 (store atmosphere) had a positive effect on the decision purchasing in fashion product at Abvistore. Hypothesis testing showed that social media promotion had no significant effect on purchasing decisions for Abvistore fashion products in Tanon, Sragen. Product quality has a significant influence on purchasing decisions for Abvistore fashion products in Tanon, Sragen. Store atmosphere has a significant influence on purchasing decisions for Abvistore fashion products in Tanon, Sragen. The F-test stated that the research model of he influence of independent variables on the dependent variable was correct. The coefficient of determination test shows that social media promotion, product quality and store atmosphere was able to explain purchasing decisions by 53.2%.